Study of Antihypertensive and Antiplatelet Use in Outpatient Preeclampsia Patients at Siti Khodijah Sepanjang Hospital - Purwanti, Uchti Firda; Fandinata, Selly Septi (Faculty of Pharmacy, Universitas Gadjah Mada, 2026)
Background: Preeclampsia is a complication of pregnancy characterized by increased blood pressure and the presence of proteinuria after reaching 20 weeks of gestation. Besides that, the diagnosis of preeclampsia can be reinforced by other symptoms such as edema, impaired liver and kidney function.Objectives: This study aims to investigate the usage of antihypertensive and antiplatelet medications in outpatient preeclampsia patients at Siti Khodijah Sepanjang Hospital from January 2022 to December 2023.Methods: Data collection method is retrospective, obtained from medical records of 70 preeclampsia patients. The sampling technique using purposive sampling method according to the inclusion research criteria. Data was analyzed using Microsoft Excel 2021.Results: Data on drug usage profiles obtained during the treatment, shows that the most common combination is a combination of two antihypertensive drugs and an antiplatelet, namely metildopa (category B) + aspirin (category C), with a dosage of 500 mg + 80 mg per day. The medication regimen is S2dd1 + S1dd1, and the average duration of treatment ranges from 7 to 30 days. With this treatment, the blood pressure of preeclampsia patients experienced a change in the patient's blood pressure which decreased in 65 patients with the initial classification of mild preeclampsia being 54 patients to normal in the final preeclampsia classification of 56 patientsConclusion: This study provides several important implications for health workers in Indonesia in the management of preeclampsia disease with the use of antihypertensive and antiplatelet drugs, so that they can provide services that are in accordance with the medical needs of patients.